Pelatihan Penggunaan dan Pemeliharaan Mikroskop bagi Kelompok Guru Biologi SMA - Andi Rahmat Saleh; Hartono Hartono; Faisal Faisal; Asham Bin Jamaluddin; Irma Suryani Indries (JKM: Jurnal Kemitraan Masyarakat, 2024)
The microscope is a key tool in biology laboratories and supports various learning activities. The Community Service Activity (PKM) was conducted to enhance the knowledge, insight, and skills of biology teachers in using and maintaining microscopes. The event took place on October 29, 2023, at the Biology Department, Faculty of Mathematics and Natural Sciences, Makassar State University, and involved 13 high school biology teachers from South Sulawesi province. The training consisted of three stages: material delivery, practical training, and evaluation of the participants' performance. The observations during the PKM revealed that the training materials and activities effectively improved the skills of the biology teachers in using and maintaining microscopes. The biology teachers responded positively to the training activities, and the PKM activities ran smoothly, achieving the expected goals.